ANALISIS TENTANG TIPE BUDAYA POLITIK MAHASISWA UNIVERSITAS RIAU - Rindi Septia Dewi; Sri Erlinda; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is in background with the role of the student begins to fade. This happens because of the culture of modernization and globalization that tends to erode the idealism and awareness of the nation and state. Not only at the national level even at the lowest levels of student awareness which has begun to be questioned. The students tend to be apathetic to issues that occur in the community. The formulation of this research problems were whether of the type of political culture of the students of Universitas Riau and what factors that affect the political culture of the students of Universtias Riau?. The aims of this research is to determine the political culture of the students of Universitas Riau and what factors that affect the political culture of the students of Universitas Riau. Based on the research findings of this research can be concluded that the percentage of respondents' recapitulation of answers questionnaire about the analysis of the type of political culture of the students of Universitas Riau which is answers on the type of parochial political culture that